What's new in paediatric hypertension?. Issue 1 (17th August 2017) - Lalji, Rowena; Tullus, Kjell
Abstract : Paediatric hypertension predisposes to hypertension and cardiovascular disease in adult life. Despite clear guidelines, there remains a lack of screening. Diagnosis remains challenging given the high rate of false-positive high blood pressure (BP) readings at a single visit; thus, multiple visits are required to confirm the diagnosis. Depending on the normative data sets used, hypertension in overweight and obese children can be underestimated by up to 20%. Specific BP targets are required for subgroups such as adolescents, children with chronic kidney disease (CKD) and type 1 diabetes. High dietary salt intake is a risk factor for cardiovascular disease. Given the rise in processed food consumption, children in developed nations are likely to benefit from salt restriction at a population-based level.